Species composition, richness, and distribution of marine bivalve molluscs in Bahía de Mazatlán, México - María del Carmen Esqueda-González; Eduardo Ríos-Jara; Cristian Galván-Villa; Fabian Rodríguez-Zaragoza (ZooKeys, 2014)
We describe the composition and distribution of bivalve molluscs from the sandy and rocky intertidal and the shallow subtidal environments of Bahía de Mazatlán, México. The bivalve fauna of the bay is represented by 89 living species in 28 families, including 37 new records and four range extensions: Lithophaga hastasia, Adula soleniformis, Mactrellona subalata, and Strigilla ervilia. The number of species increases from the upper (44) and lower intertidal (53) to the shallow subtidal (76), but only 11 (17%) have a wide distribution in the bay (i.e., found in all sampling sites and environments). The bivalve assemblages are composed of four main life forms: 27 epifaunal species, 26 infaunal, 16 semi-infaunal, and 20 endolithic. A taxonomic distinctness analysis identified the sampling sites and environments that contribute the most to the taxonomic diversity (species to suborder categories) of the bay. The present work increased significantly (31%) to 132 species previous inventories of bivalves of Bahía de Mazatlán. These species represent 34% of the bivalve diversity of the southern Golfo de California and approximately 15% of the Eastern Tropical Pacific region.